3(n + 3) = -4n + 30

1 answer

To solve the equation \( 3(n + 3) = -4n + 30 \), we will first expand and simplify both sides.

Starting with the left-hand side:

\[ 3(n + 3) = 3n + 9 \]

Now, the equation becomes:

\[ 3n + 9 = -4n + 30 \]

Next, we will add \( 4n \) to both sides to combine the \( n \) terms:

\[ 3n + 4n + 9 = 30 \] \[ 7n + 9 = 30 \]

Now, subtract \( 9 \) from both sides:

\[ 7n = 30 - 9 \] \[ 7n = 21 \]

Finally, divide both sides by \( 7 \):

\[ n = \frac{21}{7} = 3 \]

Thus, the solution is:

\[ \boxed{3} \]